Investiation of Meteorological Parameters Affecting Wind Speed Using Different Regression Techniques - Emeksi̇z, Cem; Demi̇r, İlknur (Tokat Gaziosmanpasa University, 2021)
Wind energy is the most preferred source among renewable energy sources due to its many advantages. In order to use wind energy efficiently in wind farms, the wind speed must be predicted precisely and reliably. However, there are many meteorological factors that affect the wind speed. For this reason, wind speed estimation was carried out using real-time wind speed, humidity, pressure and temperature data measured from the measurement station established in the campus of the Faculty of Engineering and Architecture of Tokat Gaziosmanpasa University. In particular, simple linear regression, multiple linear regression and multiple non-linear regression methods were used to establish a mathematical connection between meteorological data and wind speed. In this study, which aims to estimate the wind speed accurately and reliably, it has been determined that the multiple non-linear regression method comes to the fore and makes estimation with a lower error rate. As a result of the year-based analyzes, the lowest error (Root mean square error, RMSE) was observed in the Temperature-Humidity group with 0.062, and the highest error was observed in the Temperature-Pressure group with 0.068 RMSE.

Rüzgar enerjisi sahip olduğu birçok avantajdan dolayı yenilenebilir enerji kaynakları arasında en çok tercih edilen kaynak olmaktadır. Rüzgar çiftliklerinde rüzgar enerjisinin verimli kullanılabilmesi için rüzgar hızının hassas ve güvenilir bir şekilde tahmin edilmesi gerekmektedir. Fakat rüzgar hızına etkiyen birçok meteorolojik faktör vardır. Bu nedenle Tokat Gaziosmanpaşa Üniversitesi Mühendislik ve Mimarlık Fakültesi yerleşkesinde kurulan ölçüm istasyonundan ölçülen gerçek zamanlı rüzgar hızı, nem, basınç ve sıcaklık verileri kullanılarak rüzgar hızı tahminlemesi gerçekleştirilmiştir. Özellikle meteorolojik veriler ile rüzgar hızı arasında matematiksel bir bağlantı kurmak için basit lineer regresyon, çoklu lineer regresyon ve çoklu non-lineer regresyon yöntemleri kullanılmıştır. Rüzgar hızının doğru ve güvenilir bir şekilde tahminlenmesi amaçlanan bu çalışmada çoklu non-lineer regresyon yönteminin ön plana çıktığı ve daha düşük hata oranı ile tahminleme yaptığı belirlenmiştir. Yıl bazlı yapılan analizler sonucunda ise en düşük hata (ortalama karesel hatanın karekökü, RMSE) 0.062 ile Sıcaklık-Nem grubunda, en yüksek hata ise 0.068 ile Sıcaklık-Basınç grubunda görülmüştür.
Keywords: Yenilenebilir enerji; Rüzgar hızı tahmini; Regresyon analizi; Engineering; Mühendislik; Renewable energy; Wind speed estimation; Regression analysis; 13. Climate action; 7. Clean energy